In situ degradability of dry matter from four forage protein plants: Erythrina variegata, Leucaena leucocephala, Moringa oleifera and Neonotonia wightii - Martínez-Melo, J.; Fontes Marrero, Dayami; Mazorra Calero, C.A.; Valenciaga, Daiky; Acosta, Y.; Serrano, J.O. (Cuban Journal of Agricultural Science, 2025)
To determine the in situ degradability of dry matter of: Erythrina variegata, Leucaena leucocephala, Moringa oleifera and Neonotonia wightii (Glycine), two cannulated male sheep of Pelibuey breed, weighing 36 kg, were used. Incubation times of 0, 8, 16, 24, 36, 48 and 72 hours were used and the rumen bag method was applied. The trend in ruminal degradability was increasing in the order: Glycine, Leucaena, Erythrina and Moringa. For Moringa, a higher value of ruminal degradability was obtained at 72 hours, greater than 80 %, as well as effective degradability (59.35 %). It is concluded that, although the plants are promising for ruminant feeding, Moringa showed superior indicators in the parameters of ruminal degradation and in situ degradability of dry matter. Ruminal degradability studies are required that relate cutting frequency and secondary metabolite effects.